2023
DOI: 10.3390/ijms24087481
|View full text |Cite
|
Sign up to set email alerts
|

Retinitis Pigmentosa: Current Clinical Management and Emerging Therapies

Abstract: Retinitis pigmentosa (RP) comprises a group of inherited retinal dystrophies characterized by the degeneration of rod photoreceptors, followed by the degeneration of cone photoreceptors. As a result of photoreceptor degeneration, affected individuals experience gradual loss of visual function, with primary symptoms of progressive nyctalopia, constricted visual fields and, ultimately, central vision loss. The onset, severity and clinical course of RP shows great variability and unpredictability, with most patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 340 publications
0
12
0
Order By: Relevance
“…The latter may be also of interest for emerging CRB1 gene-augmentation therapy or mutational correction by allelic substitution via CRISPR/Cas9-mediated homology-directed repair or base editing, 62,63 because these therapeutic approaches are accompanied by immune activation when administered intravitreally or subretinally. 64 It would be important to determine to what extent the inflammatory markers identified in this study may help understand the side effects of gene therapy, such as increased chorioretinal atrophy that has recently been described after gene therapy using voretigene neparvovec for RPE65 -associated retinal dystrophies. 65,66 A major source of plasma complement components is the liver, but complement proteins are also produced and expressed in the retina, as well as by immune cells and various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The latter may be also of interest for emerging CRB1 gene-augmentation therapy or mutational correction by allelic substitution via CRISPR/Cas9-mediated homology-directed repair or base editing, 62,63 because these therapeutic approaches are accompanied by immune activation when administered intravitreally or subretinally. 64 It would be important to determine to what extent the inflammatory markers identified in this study may help understand the side effects of gene therapy, such as increased chorioretinal atrophy that has recently been described after gene therapy using voretigene neparvovec for RPE65 -associated retinal dystrophies. 65,66 A major source of plasma complement components is the liver, but complement proteins are also produced and expressed in the retina, as well as by immune cells and various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…RP was also reported to be one of the predisposing factors of late spontaneous IOL-capsular bag complex dislocation ( 49 , 51 ). On the other hand, recently, numerous studies have confirmed the role of inflammatory response and cytokines, such as platelet-derived growth factor AA (PDGF-AA), matrix metalloproteinase-2 (MMP-2), MMP3, MMP-7 and MMP-8, in the development of ACCS following cataract surgery in RP patients ( 52 , 53 ). That may reveal the pathogenesis of ACCS in RP patients.…”
Section: Influencing Factors For Accsmentioning
confidence: 99%
“…That may reveal the pathogenesis of ACCS in RP patients. Additionally, the liquefaction of the vitreous may lead to postoperative insufficient support of the capsular bag, which could potentially become one of the reasons for IOL dislocation ( 53 ). Further works are required to determine the conclusive evidence of the pathogenesis to identify targeted and effective therapeutics, and specific prevention to limit the occurrence of surgical complication ( Figure 2 ).…”
Section: Influencing Factors For Accsmentioning
confidence: 99%
“…Masuda and colleagues 18,19 exploring cortical responses to visual stimuli consisting of checkerboards and scrambled or intact faces, showed that when RP patients were asked to passively look at the stimuli, they exhibited either large unresponsive zones of V1 or responsive zones with reduced brain responses. Studies aimed at clinically assessing visual eld loss in RP used automated static perimetry test 20,21 together with a wide range of clinical tests, separately examining central and peripheral vision 22 . In the clinical context, ophthalmological tests of central and peripheral vision de ciencies are separated and acuity assessment is based exclusively on perception of stationary black stimuli on a white board, as in the Snellen letter chart.…”
Section: Introductionmentioning
confidence: 99%